Hubungan Pola Makan Ibu Hamil Dengan Kejadian Kehamilan Risiko Tinggi Pada Ibu Hamil Trimester III Di Puskesmas Muara Kaman Tahun 2023 - Desiyanti, Eka; Jasmawati, Jasmawati; Nulhakim, Lukman (Akademi Kebidanan Bunga Husada Samarinda, 2023)
Maternal mortality cannot be separated from high-risk pregnancies. Pregnant women are at high risk for a number of diseases. As a result, mothers experience anemia, CED, and babies experience LBW, birth defects, stunting, and even death. High-risk pregnancies are influenced by many factors, namely proper nutrition during pregnancy. The aim of the study was to determine the relationship between the diet of pregnant women and the incidence of high-risk pregnancies in third-trimester pregnant women at the Muara Kaman Health Center in 2023. This research used a descriptive quantitative study using a cross-sectional design. using the total sampling technique, the number of samples was 51 third trimester pregnant women who met the inclusion and exclusion criteria. The results showed that there was no significant relationship between the diet of pregnant women and the incidence of high-risk pregnancies in third trimester pregnant women at the Muara Kaman Health Center with a p-value of 0.388. Provide education to prospective pregnant women or pregnant women regarding the importance of good nutritional intake before and during pregnancy